A Field Guide to Mechanisms: Part I. Issue 4 (April 2014) - Andersen, Holly
Abstract In this field guide, I distinguish five separate senses with which the term 'mechanism' is used in contemporary philosophy of science. Many of these senses have overlapping areas of application but involve distinct philosophical claims and characterize the target mechanisms in relevantly different ways. This field guide will clarify the key features of each sense and introduce some main debates, distinguishing those that transpire within a given sense from those that are best understood as concerning distinct senses. The 'new mechanisms' sense is at the center of most of these contemporary debates and will be treated at greater length; subsequent senses of mechanism will be primarily distinguished from this one. In part I of this paper, I distinguish two senses of the term 'mechanism', both of which are explicitly hierarchical and nested in character, such that any given mechanism is comprised of smaller sub‐mechanisms, in turn comprised of yet smaller sub‐sub‐mechanisms and so on. While both of the senses discussed here are anti‐reductive, they differ in their focus on scientific practice versus metaphysics, in the degree of regularity they attribute to mechanisms, and in terms of their relationships to the discussions of mechanisms in the history of philosophy and science.